2017
DOI: 10.1007/s00464-017-5545-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel esophageal stent for treatment of cervical anastomotic leakage after esophagectomy

Abstract: Placement of the novel esophageal covered stent is a minimally invasive, efficacious treatment option for the patients with cervical anastomotic leakage after esophagectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…After removing 2,382 duplicates, 2,733 titles and abstracts were screened, and 126 articles underwent full-text assessment, of which 32 were included in the systematic review (Fig. 1) [21‒52]. We also checked the reference list of previous systematic reviews on the topic but found no further relevant studies.…”
Section: Resultsmentioning
confidence: 99%
“…After removing 2,382 duplicates, 2,733 titles and abstracts were screened, and 126 articles underwent full-text assessment, of which 32 were included in the systematic review (Fig. 1) [21‒52]. We also checked the reference list of previous systematic reviews on the topic but found no further relevant studies.…”
Section: Resultsmentioning
confidence: 99%
“… 26 , 27 , 28 However, traditional esophageal stents are indicated for the thoracic AFs rather than the cervical AFs because of the potential patient intolerance or stent migration as the residual esophagus is too short for the placement of the stents, and the stent migration inevitably leads to the failure to stop the leakage. 18 Custom-designed stents have been developed and reported to be effective for cervical anastomotic fistula, however, the study sample size is quite small, and this novel stent is unavailable commercially. 18 In our study series, covered stent was attempted and failed in only 1 patient (pt.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Custom-designed stents have been developed and reported to be effective for cervical anastomotic fistula, however, the study sample size is quite small, and this novel stent is unavailable commercially. 18 In our study series, covered stent was attempted and failed in only 1 patient (pt. no.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our series, leaks after TTE were managed with a covered stent (7/10), while early post-operative leaks were treated with reoperation. Leaks after THE were treated conservatively (7/11) with the controlled fistula technique, opening of the cervical wound and packing and daily dressing rather than with a stent because of the unavailability of a conventional stent at the cervical location [30].…”
Section: Discussionmentioning
confidence: 99%